2017
DOI: 10.17556/erziefd.338356
|View full text |Cite
|
Sign up to set email alerts
|

Yabancı Dil Olarak Türkçe Öğrenenlerin Yazma Özyeterlikleri ile Yazılı Anlatım Becerileri

Abstract: In the study, the relationship between writing self-efficacy perceptions and writing expression skills of students learning Turkish at B2 level at Inonu University TOMER and Syrian refugee camp TOMER was determined. As a data collection tool in the study, "The Writing Self-Efficacy Scale for Students Learning Turkish as a Foreign Language" developed by Güngör and Kan (2015), "Written Expression (Writing) Evaluation Form for B2 Level Users" created by Demir (2013a: 568) and Personal Information form were used. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 12 publications
1
8
0
3
Order By: Relevance
“…Benzer şekilde Türkiye' de yazma öz yeterliliğini değerlendiren sınırlı sayıda çalışma tespit edilmiştir. Bu konuda literatür çalışması şeklinde oluşturulan (Akar, 2008) araştırmalar olduğu gibi ortaokul öğrencilerinin yazma öz yeterliliklerini ölçmek amacıyla ölçek geliştirme ve uygulamayı içeren çalışmalar (Demir, 2011;Büyükikiz, 2012;Şengül, 2013;Korkmaz, 2015;Özonat, 2015;Altunkaya ve Ateş, 2017;Akar ve Özber, 2018); farklı yazma uygulamalarının yazma öz yeterliliklerine olan etkileri (Manay, Türkel ve Savaş, 2017) incelenmiştir. Benzer çalışmalar Türkiye dışında gerçekleştirilmiştir.…”
Section: Conclusion and Discussionunclassified
“…Benzer şekilde Türkiye' de yazma öz yeterliliğini değerlendiren sınırlı sayıda çalışma tespit edilmiştir. Bu konuda literatür çalışması şeklinde oluşturulan (Akar, 2008) araştırmalar olduğu gibi ortaokul öğrencilerinin yazma öz yeterliliklerini ölçmek amacıyla ölçek geliştirme ve uygulamayı içeren çalışmalar (Demir, 2011;Büyükikiz, 2012;Şengül, 2013;Korkmaz, 2015;Özonat, 2015;Altunkaya ve Ateş, 2017;Akar ve Özber, 2018); farklı yazma uygulamalarının yazma öz yeterliliklerine olan etkileri (Manay, Türkel ve Savaş, 2017) incelenmiştir. Benzer çalışmalar Türkiye dışında gerçekleştirilmiştir.…”
Section: Conclusion and Discussionunclassified
“…The findings of many studies demonstrated the relationship between writing performance and writing self-efficacy perceptions. In studies conducted in different populations, self-efficacy perceptions were found to affect writing performance (see Altunkaya & Ateş, 2017;Bulut, 2017;Hetthog &Teo, 2013;Nicolaidou, 2012;Xu & Baek., 2011). Research on the self-efficacy perceptions of students from elementary school to higher education level revealed different results related to the gender variables.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar context, Aydin and Duğan (2018) determined that female university students had higher efficacy in applying grammar rules than male students did. Altunkaya and Ateş (2017) focused on the relationship between the writing self-efficacy and writing performance of learners of Turkish as a foreign language, and indicated that female learners had higher scores. Although various studies in the literature Bağci (2007), Özdemir (2008), Yilmaz, Yiğit, Kaşarci (2012), Baş & Şahin (2012) reported that writing self-efficacy perceptions are more positive in women, some studies Ekici (2008), Ülper & Bağci (2012), Eggleston (2017) could not reveal a difference in self-efficacy based on gender.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, writing often turns into a difficult process for both second (SL) or foreign language (FL) learners and first language (L1) learners (Belet & Yaşar, 2007;Idris, 2009;Mah et al, 2017). This also applies to for international students who come to Turkey from different countries and learn Turkish as a second language (TSL) (Tiryaki, 2013;Altunkaya & Ateş, 2017). Writing skill has a complex structure consisting of cognitive, affective and psychomotor dimensions.…”
Section: Introductionmentioning
confidence: 99%